A novel signature of combing cuproptosis- with ferroptosis-related genes for prediction of prognosis, immunologic therapy responses and drug sensitivity in hepatocellular carcinoma - Zhao, Chuanbing; Zhang, Zhengle; Jing, Tao (Frontiers in Oncology, 2022)
Abstract Our study aimed to construct a novel signature (CRFs) of combing cuproptosis-related genes with ferroptosis- related gene for prediction of prognosis, responses of immunotherapy and drug sensitivity of hepatocellular carcinoma (HCC) patients. RNA-seq and corresponding clinical data of HCC patients were downloaded from TCGA & ICGC databases. CRFs was constructed by using LASSO algorithm. Prognostic analysis, functional analysis ,somatic mutation analysis, immune profiles analysis, and stemness analysis were performed between the low- and high-risk groups. Subsequently, drug sensitivity was screened for the high- and low-risk groups,respectively. The CRFs included 7 genes (G6PD , NRAS, RRM2, SQSTM1, SRXN1, TXNRD1 and ZFP69B). A multivariate Cox regression analysis demonstrated that CRFs was an independent risk factor for prognosis. And these HCC patients in high-risk group tended to present poorer prognosis. And the functions enriched in low-risk group differed from those in the other group.Notably, patients in the high-risk group presented significant state of immunosuppression. We found that patients in the high-risk group may achieve greater outcomes after receiving immunotherapy. Besides, higher tumor mRANsi was seen in high-risk group. Finally, 6 sensitive drugs were screened for patients in the high-risk group while 1 sensitive drug were screened for patients in the low-risk group. Of great importance, patients in the high-risk group may benefit more from the administration of Paclitaxel. CRFs may be regarded not only as a marker of poor prognosis, but also as an excellent predictor of immunotherapy response and drug sensitivity in HCC, which is worthy of clinical promotion.